Risk Factors Associated With Survival to Hospital Discharge of 54 Horses With Fractures of the Radius. Issue 8 (12th October 2015) - Stewart, Suzanne; Richardson, Dean; Boston, Ray; Schaer, Thomas P.
Abstract : Objective: To determine (1) survival to discharge of horses with radial fractures (excluding osteochondral fragmentation of the distal aspect of the radius and stress fractures); and (2) risk factors affecting survival to hospital discharge in conservative and surgically managed fractures. Study Design: Case series. Animals: Horses (n = 54). Methods: Medical records (1990–June 2012) and radiographs of horses admitted with radial fracture were reviewed. Horses with osteochondral fragmentation of the distal aspect of the radius or stress fractures were excluded. Evaluated risk factors were age, fracture configuration, surgical repair method, surgical duration, hospitalization time, implant failure rate, and surgical site infection (SSI) rate. Results: Of 54 horses, overall survival to discharge was 50%. Thirteen (24%) were euthanatized on admission because of (1) fracture severity; (2) presence of an open fracture; or (3) financial constraints. Fourteen (26%) horses with minimally displaced incomplete fractures were conservatively managed and 12 (86%) survived to discharge. Twenty‐seven (50%) horses had surgical treatment by open reduction and internal fixation (ORIF) and 15 (56%) survived to hospital discharge. Open fractures were significantly more likely to develop SSI ( P  = .008), which also resulted in a 17‐fold increase in implant failure ( P  < .005). Six of 8 surgically managed horses with an open fracture did not survive to discharge. Outcome was also adversely affected by age ( P  <  .005) and surgical duration >168 minutes ( P  < .027). Presence of SSI trended toward a decreased survival rate ( P  = .09). Conclusion: Prognosis for survival to discharge with minimally displaced incomplete fractures is good. Young horses have a good prognosis survival to discharge for ORIF, whereas ORIF in adult horses has a poor prognosis and SSI strongly correlates with catastrophic implant failure.